An Analysis of Urban Secondary School Studentsa Interest in Teaching Profession in South-Western Nigeria (Global Journal of Human-Social Science, 2011)
The study analyzed Senior Secondary School Students interest in teaching profession in Oyo city South-western Nigeria Data used for this study were collected through questionnaire administration for 270 students randomly selected in nine secondary schools in the study area A vocational interest inventory of items constructed and validated by the researchers with reliability co-efficient of 0 78 obtained was the instrument used for data collection The data collected from the interviews were analyzed using descriptive statistics and chi-square test The result of finding showed that 68 5 of the sampled population had interests in a profession that involved dealing with children while 27 6 had interest in becoming career teacher but 78 3 of sampled population preferred teaching as a career to any other profession if teachers remuneration were highly increased There was no relationship between gender and response to profession that involves dealing with children but there was significant relationship between students interest in teaching profession and increase in teachers remuneration The study concluded that the students have weak feeling of interest to be career teacher owing to poor affinity of their parents and teachers to teaching profession poor work environment and inducement in teaching profession The study therefore recommended the needs for proper coordination of the necessary machineries towards innovation in policies that can arouse young people s interest in teaching profession
Keywords: Profession; Remuneration Students; Teacher